Capsular polysaccharide of Mycoplasma mycoides subsp. capri contributes to phenotypic diversity promoting distinctive immune responses - Yimthin, T.; Bourgeon, M.; Zhang, J.; Eggerschwiler, L.; Siegenthaler, R.; Schieck, Elise; Torres-Puig, S.; Ruggli, N.; Démoulins, T.; Jores, Joerg (Public Library of Science, 2025)
Mollicutes are minute cell wall less bacteria encompassing important pathogens. We show that pathogenic Mycoplasma mycoides subsp. capri (Mmc) can switch expression of capsular polysaccharide (CPS), which creates phenotypic diversity and has dramatic repercussions on immune responses. To characterize the immune responses, we employed the highly virulent Mmc strain GM12 as well as an engineered CPS-deficient mutant in a set of assays employing primary blood cells from its native caprine host and cattle. Primary blood cells stimulated with GM12 showed only very moderate effects on cell viability as well as activation marker expression supporting an immunological furtiveness-like lifestyle. Interestingly, GM12 showed the capacity to survive and resist inside monocyte-derived macrophages (MDMs), which fosters dissemination and persistence in the host. Stimulation with the CPS-deficient mutant which exposes surface proteins including lipoproteins, increased cell death, strongly suppressed expression of major histocompatibility complex on antigen-presenting cells and induced secretion of several pro-inflammatory cytokines/chemokines which is a clinical hallmark in infected animals. Moreover, the CPS-deficient mutant elicited inflammatory cell death in MDMs. In conclusion, we showed that Mmc can switch the expression of CPS, which leads to different immunological trajectories paving the way for clinical disease, dissemination and persistence in the host.